A population-based study of race-specific risk for placental abruption - Stamilio David M; DeFranco Emily A; Shen Tammy T; Chang Jen; Muglia Louis J (BMC, 2008)
Abstract Background Efforts to elucidate risk factors for placental abruption are imperative due to the severity of complications it produces for both mother and fetus, and its contribution to preterm birth. Ethnicity-based differences in risk of placental abruption and preterm birth have been reported. We tested the hypotheses that race, after adjusting for other factors, is associated with the risk of placental abruption at specific gestational ages, and that there is a greater contribution of placental abruption to the increased risk of preterm birth in Black mothers, compared to White mothers. Methods We conducted a population-based cohort study using the Missouri Department of Health's maternally-linked database of all births in Missouri (1989-1997) to assess racial effects on placental abruption and the contribution of placental abruption to preterm birth, at different gestational age categories (n = 664,303). Results Among 108,806 births to Black mothers and 555,497 births to White mothers, 1.02% (95% CI 0.96-1.08) of Black births were complicated by placental abruption, compared to 0.71% (95% CI 0.69-0.73) of White births (aOR 1.32, 95% CI 1.22-1.43). The magnitude of risk of placental abruption for Black mothers, compared to White mothers, increased with younger gestational age categories. The risk of placental abruption resulting in term and extreme preterm births (< 28 weeks) was higher for Black mothers (aOR 1.15, 95% CI 1.02-1.29 and aOR 1.98, 95% CI 1.58-2.48, respectively). Compared to White women delivering in the same gestational age category, there were a significantly higher proportion of placental abruption in Black mothers who delivered at term, and a significantly lower proportion of placental abruption in Black mothers who delivered in all preterm categories (p < 0.05). Conclusion Black women have an increased risk of placental abruption compared to White women, even when controlling for known coexisting risk factors. This risk increase is greatest at the earliest preterm gestational ages when outcomes are the poorest. The relative contribution of placental abruption to term births was greater in Black women, whereas the relative contribution of placental abruption to preterm birth was greater in White women.